Analog front-end: UWB chipless RFID system - Hossain, A.K.M. Zakir; Ibrahimy, Muhammad Ibn; Motakabber, S. M. A. (IIUM Press, International Islamic University Malaysia, 2017)
The invention of the Radio Frequency Identification (RFID) has introduced many advantages in the product tagging, object tracking and supply chain management comparing with the barcode system. Allocation of the UWB frequency range has given the RFID researchers another edge to include more bits for the inscription due to the wideness of the band and nowadays research on RFID is at the forefront to replace the barcode system. Often, it has been seen from literature that in the RFID system, the main focus is on the tag and how it can be read. Many researchers tried to read the backscattered data from the passive UWB tag with highly sophisticated test instrumentations such as, vector network analyzers (VNA), spectrum analyzers etc. In the UWB RFID readers, that can successfully read the microstrip resonator type tag, the generation of the chirp signal (and also in the tag space) limits the inclusion of more bits to the system. Inclusion of more bits needs more bandwidth which leads to the difficulties to design large bandwidth chirp signal. In literature it is also found that there are very little emphasis given on the development on the reader while developing a RFID system and how to make it simple and energy efficient. UWB RFID system is totally dependent on the constant chirp generation from the UWB RFID reader. With respect to the design of the tag, the bits can be spread over the entire bandwidth (BW) which goes up to 5 GHz. To detect the bits, the entire bandwidth needs to be swept while the only concerning frequencies are needed for detection and rest of the BW will be idle. From the theory of the mixer topology it is well known that with the fundamental frequency, two different main tones can be generated. These two tones are totally separate frequencies and can operate individually by separating them with narrow band pass filters. With this idea, by cascading as many mixer-filter configurations eight different frequencies are generated from 5 to 7 GHz. The generation is only limited on those concerning frequencies which the bits are allocated on a microstrip resonator type tag. A duty cycle of 50% is kept while switching different frequencies. Since the generated interrogation signal is a ‘chirp and hold’ signal, in this process the entire BW sweep is not necessary. Due to 50% on time, the EIRP of the reader is doubled and consequently the reading range is increased. The reader is also made less complex and easy to design. A new type of linear resonator for the UWB passive tag also designed and developed to fit with the designed reader front-end. The result shows the 8-bit tag’s resonator section occupies 19.22 mm2/bit. The new design has reduced the area/bit up to 20% from the recent research.